The Investigation How Students’ Team Achievement Development Strategy Improves the Students' Interest in Speaking English - Jelimun, Maria Olga (Yayasan Ahmar Cendekia Indonesia, 2025)
This research aimed to investigate how Student Teams-Achievement Divisions (STAD) technique was able to improve the students’ interest in speaking English. This research is a quasi-experimental where the data collection is done by using tests, namely pre tests and post tests. In order to conclude the data, researchers analyzed them statistically. The participants comprised students enrolled in the eleventh grade Language Program, totaling 32 individuals, inclusive of 13 male and 19 female students of SMAN 1 Poco Ranaka, East Manggarai, Flores NTT. The pre- and post-test results of the 19 students who were looking at the impact of Student Teams Achievement Divisions (STAD) are shown in Table 3's descriptive statistics. With a standard deviation of 10.096, the pre-test mean score was 67.579. The pre-test scores yielded a standard error (SE) of 2.316 and a coefficient of variation of 0.149, which represents the relative variability of the scores. In a similar vein, the post-test results showed a significantly higher mean score of 77.579, suggesting that performance had improved after the intervention. The post-test scores had a standard deviation of 10.394 and a standard error of 2.385. With a coefficient of variation of 0.134, the post-test scores had a somewhat lower coefficient of variance than the pre-test results. The accuracy, variability, and central tendency of the pre- and post-test scores are all well-represented by these descriptive statistics. The rise in the average score between the pre- and post-tests indicates that the STAD intervention had a beneficial effect on students' performance..